Isolation and Characterization of a Novel ?-Conotoxin from the Venom of Vermivorous Cone Snail Conus parvatus - Balamurugan, K.; Dey, Akalaka; Kalaichelvan, V.K.; Raju, S. (Asian Journal of Chemistry, 2010)
In this paper, the isolation, characterization and total synthesis of a small peptide ligand for nicotinic acetylcholine receptors (nAChRs) are reported, which targets the neuromuscular nicotinic acetylcholine receptor with high affinity in frog. The new peptide is α-conotoxin obtained from the snail Conus parvatus which preys on polychaete worms. The sequence of the peptide is: Gly-Cys-Cys-His-Pro-Arg-Cys- Gly-lys-Arg-Tyr-Asp-Cys-NH2. The peptide shows slight homologous sequence difference from all α-conotoxins of fish-hunting Conus, but its disulfide-bridging is similar: [2-7; 3-13], It is suggested that cone venoms may provide an array of ligands with selectivity for various nAChR subtypes.